Analisis Media Monitoring Terhadap Pemberitaan Brand Kosmetik Emina Pada Periode Maret - April 2024 - Hanna Aliya Khairunnisa (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
According to data from the Ministry of Industry, the growth of Indonesia's cosmetics industry has continued to expand by up to 20% since 2017. Emina, a cosmetic brand from PT Paragon Technology and Innovation, is one of the brands targeting a young audience. Emina has demonstrated its popularity by achieving sales revenue totaling IDR 1.5 billion in the first two weeks of September 2022 through the Shopee marketplace. Additionally, Emina has garnered over 3 million followers on Shopee and has an average product rating of 4.9 out of 5 from 2.5 million reviews. This success highlights the need for media monitoring as a means to track and analyze brand and product insights on the internet. By utilizing social media monitoring analytical tools and collecting timeline-based data from Brand24, this study employs Netnography as a descriptive qualitative research method.